Development of integrated criteria for selection and monitoring of subcontractors in Malaysia - Lew, Yoke Lian (2017)
Subcontracting practice has become a norm in current construction industry. A performance of construction work is strongly dependant on subcontractors. Problems arising from subcontracting may cause vast influence to the construction project, and may affect the operation of the general contractor’s organisation. Previous studies on subcontractors focused on the single phase of subcontracting practice, either on registration, selection of subcontractors, or on monitoring of subcontractors without much integration of different phases. This study aims to fill the gap between these phases. The key criteria used by general contractors in selecting subcontractors before job-awarding, and key criteria used for monitoring of subcontractors during construction work was first identified followed by discovery of the interrelationships between the criteria used for selection of subcontractors and the monitoring of subcontractors during construction stage. The interrelationships between the criteria and effects of these criteria on the project performance were investigated simultaneously using a single model based on structural equation modelling (SEM) method. Data obtained from 162 G7 contractors in Malaysia were analysed. The final model discovered four major criteria that are essential in the selection of subcontractors, namely, ‘communication’, ‘relationship’, ‘general obligation’, and ‘resource management’ of a subcontractor. Meanwhile, the major criteria for monitoring of subcontractor are ‘workmanship’, ‘awareness of environment, health and safety’, and ‘communication and relationship’. The four criteria for selection of subcontractors were found to be interrelated among themselves and influence the criteria used to monitor subcontractors during the construction stage. The study also reveals that the criteria used to monitor subcontractor were found to influence the performance of a project. The interrelationships discovered in this study were used to develop a web-based system that allows the general contractor to select the subcontractors, monitor the subcontractors during construction stage, and predict the project performance using a single system. The gap between the criteria used for selection and monitoring of subcontractors is filled with this proposed web-based system.